A multilevel cognitive model of coming out - Dyrmo, Tomasz (Papers in Linguistics, 2022)
The article explores coming out narratives, as its starting point employing a multilevel approach to this phenomenon in line with a model proposed by Zoltan Kӧvecses (2017), applying image schemas, domains and frames, and metaphor scenarios. It describes how these levels interact with each other to construe the metaphoric meaning at the level of mental structures which motivate linguistic choices in coming out narratives concerning sexual orientation or gender identity. The analysis of the linguistic material reveals that highly individualised coming out narratives are underpinned by less complex cognitive mechanisms.